Climatologia da pluviosidade na bacia hidrográfica do Rio Paranaíba - Santos, Danniella Carvalho dos (2016)
The main aim of this research was to study pluviosity in the Paranaíba Riverbasin, especially concerning the variability frame and trends. For this end, we used data from 22 pluviometric stations of the Agência Nacional da Águas- ANA(National Water Agency)spatially distributed throughout the basin area. The data comprised the years 1979-2013, which is a historical series of 35 years, and was downloaded through the ANA website and tabulated using the Hydro 1.2 software (2015) and Excel. After tabulation process were applied based methodologies for statistical analysis of annual variability, monthly, daily and seasonal rainfall in the basin beyond the trend analysis. Results of this research showed that the annual rainfall averageis 1491 mm. Seasonality is a hallmark and rainfall variability occurs spatially and temporally. Rains are accumulated in the rainy season accumulating 85% of the annual volume in the basin. In daily analysis it was found that the daily rainfall above 30 mm occur in only 3% of the time. Dry season comprises 15% of the rainfall. Trend analysis using linear regression pointed to a downward trend in rainfall in 46% of jobs, stability in 18% of posts and increased rainfall by 36%. As for the analysis using the sign test indicated that 32% of the analyzed rainfall stations showed an increasing trend of rainfall over the time series and 68% of stations showed downward trend. This research is important because shows how rainfall worksin the area of the Paranaiba basin, and may be used to develop better management of natural resources and the area through public policies for this purpose.